Effect of manganese stoichiometry at B-site on magneto-transport and magnetic properties of La0.67Sr0.33MnO3manganites. Issue 9 (1st May 2022) - Swetha, K.; Bharadwaj, S.; Chelvane, J. Arout; Afzal, Hasan; Venkatesh, R.; Kumar, K.V. Siva; Yanapu, Kalyana Lakshmi
Abstract: To study the effect of manganese non-stoichiometry at B-site, a series of manganites with compositional formula La0.67 Sr0.33 Mn1±x O3 (where x = 0, 0.05 and 0.1) was synthesized by oxalate precursor method. X-ray diffraction data confirm the rhombohedral structure of La0.67 Sr0.33 Mn1±x O3 along with minor phases of Mn3 O4 . The average grain size is found to be 266 nm for x = 0 whereas its magnitude decreases with excess or deficiency in manganese concentration. An increase in the manganese non-stoichiometry leads to the coexistence of ferromagnetic and antiferromagnetic interactions. The effect of Mn1±x on the magnetotransport properties could be understood on the basis of collective behaviour of magnetic spins, double exchange mechanism and ratio of Mn 4+ /Mn 3+ ions. A crossover from negative to positive magnetoresistance behavior above metal-insulator transition temperature was observed for LSP-0.95 sample, whereas a positive magnetoresistance over the entire temperature region was noticed for LSP-1.10 sample.